ANALISIS PENGARUH PROFITABILITAS LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP SUSTAINABILITY REPORTING (studi kasus pada perusahaan perbankan yang terdaftar di bursa efek indonesia tahun 2021-2023) - Marcelena, Anisa; Wahyuningsih, Panca (STIE PENA, 2024)
This research aims to find out how Profitability, Leverage and Company Size influence Sustainability Reporting in banking sector companies listed on the Indonesia Stock Exchange (BEI) for the 2021-2023 period.The sampling technique in this research used a purposive sampling technique, based on criteria determined by the number of samples collected as many as 81 companies. The test technique used is the classical assumption test including normality, multicollinearity, heteroscedasticity test, and autocorrelation test. The data analysis method uses the SPSS 25 program. The results of this research show that Profitability has no effect on Sustainability Reporting, Leverage has a positive and significant effect on Sustainability Reporting and Company Size has no effect on Sustainability Reporting while simultaneously Profitability, Leverage and Company Size have an effect on Sustainability Reporting. Keywords: Profitability, Leverage, Company Size and Sustainability Reporting